1987
DOI: 10.1007/bf01486964
|View full text |Cite
|
Sign up to set email alerts
|

Mothers of children with autism or communication disorders: Successful adaptation and the double ABCX model

Abstract: This study demonstrates the effectiveness of a modified Double ABCX or FAAR model in predicting successful adaptation--good marital adjustment, few maternal depressive symptoms, and an in-home rating of family functioning--in 45 families of autistic and communication-impaired children. The model consisted of severity of the handicap and other family stresses, family resources of cohesion and social support, family definition of the handicap, and adequacy of coping patterns. Canonical correlation and subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
137
2
11

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(166 citation statements)
references
References 24 publications
16
137
2
11
Order By: Relevance
“…Frequently occurring child-related stressors among parents of children with ASD or other developmental disabilities include the severity of a child's disability (Bristol, 1987;Krauss, 1993), the child's caretaking demands (Minnes, 1988), and most notably, the child's problem behaviors (internalizing and externalizing problem behaviors; Hastings, 2002;Hodapp et al, 1997). Caregiver variables such as education, financial resources, and health, have also been identified as stressors (Hauser-Cram et al, 2001;Minnes et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Frequently occurring child-related stressors among parents of children with ASD or other developmental disabilities include the severity of a child's disability (Bristol, 1987;Krauss, 1993), the child's caretaking demands (Minnes, 1988), and most notably, the child's problem behaviors (internalizing and externalizing problem behaviors; Hastings, 2002;Hodapp et al, 1997). Caregiver variables such as education, financial resources, and health, have also been identified as stressors (Hauser-Cram et al, 2001;Minnes et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…One early study found that the model was an effective way of framing family adaptation in families of children with autism or severe communication disorders (Bristol, 1987). Another study found that the model was helpful in explaining parental stress of fathers and mothers of children with intellectual disability (Saloviita, Italinna, Leinonen, 2003).…”
Section: Empowerment and Parent Gainmentioning
confidence: 99%
“…Dans le même ordre d'idées, plusieurs autres auteurs ont identifié divers facteurs liés à l'augmentation des effets du stress que génère la pathologie de l'autisme sur les familles. À ce sujet, des auteurs soutiennent que le sexe du parent (Bristrol et al, 1988;Gray & Holden, 1992;Milgram & Atzil, 1988), le degré et le type de soutien social reçu (Bristrol, 1984;Bristol, 1987;Bristol et al, 1988;Gray & Holden, 1992;Milgram & Atzil, 1988), la présence de stress additionnels (Bristrol, 1987), l'âge de l'enfant (Bristol, 1987;Gray & Holden, 1992;Hasting et al, 2005) et l'obligation de réaliser d'autres activités occupationnelles Bristol, 1987;Hasting et al, 2005) De plus, le fait de vivre avec un enfant ayant des besoins particuliers limite le temps pour les parents de pouvoir répondre à leurs propres besoins (Bouma & Schweitzer, 1990, Fox et al , 2002, Howlin, 1988. Holroy et McArthur (1976) Dans ces familles, l'estime de soi des enfants serait moins élevé et il serait plus fréquent d'y relever divers symptômes de dépression (Gold, 1993;Rodrigue et al 1993).…”
Section: Autres Facteurs Collatéraux Avec Lesquels Doivent Composer Lunclassified